Prevalence of clustering of lifestyle cardiovascular risks and its association with cardiovascular screening activities among apparently healthy government servants in ‘Wisma Persekutuan’ Kuala Terengganu, Terengganu - Mat Hassan, Nurulhuda (2015)

(untitled)
Introduction: Cardiovascular diseases are the leading cause of death and disability among men and women in nearly all nations, including Malaysia and are projected to remain the single leading cause of death up to 2030. Lifestyle cardiovascular risks such as dietary habits, physical inactivity and smoking are considered fundamental risk factors for cardiovascular disease. Some studies in developed countries have found that lifestyle risk factors occur in combination with each other and are not randomly distributed across populations. Methodology: This cross-sectional study was done from June to August 2013 to determine the prevalence of lifestyle risks, clustering of lifestyle risks, and optimal screening; to determine the association of clustering of lifestyle risks with cardiovascular screening activities among government servants in Kuala Terengganu, Malaysia. A questionnaire which consisted of a case report form, International Physical Activity Questionnaire (IPAQ) and the dietary component of WHO STEPs were used as tools. The questionnaires were distributed to 121 government servants aged ≥20 years without any established cardiovascular disease. Cardiovascular screening for a history of blood pressure, blood glucose, serum lipids and BMI measurement were done for each participant. Findings: The study response rate was 90.9% (110 of 121). Prevalence of smoking, physical inactivity and unhealthy diet were 20%, 50% and 87% respectively. Prevalence was more in the lower socio-economic group. The prevalence of clustering of lifestyle cardiovascular risks was 57%. The prevalence of optimal cardiovascular screening for age was 49%. Clustering of lifestyle risks was significantly associated with non-optimal screening (p=0.004). Other significant factors associated with non-optimal screening were female gender, age and last visit to medical practitioner more than one year. Conclusion: Measures needed to be done to promote affordable healthier diet and healthy lifestyle activities. Promotion of healthy lifestyle behaviors should be done via synergistic action of public health and primary care sectors and emphasis should be made at primary care level to screen those with multiple lifestyle cardiovascular risks in order to optimize cardiovascular disease prevention.